A participatory multi-criteria framework for freshwater ecosystems: Integrating SWOT and AHP for sustainable governance - Safira Rosyada (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The Telaga Cebong located in the Dieng Plateau of Central Java, play vital role in supporting local agriculture, ecology, and tourism. However, increasing anthropogenic pressures have led to declining water quality and ecological degradation. This study aims to formulate a sustainable management strategy for Telaga Cebong by integrating community perspective, ecological data, and institutional frameworks. Previous studies have identified eutrophication risks and sedimentation as major threats to the lake's functionality, yet a robust, integrated management strategy that incorporates local context and participatory decision-making remains absent. Drawing on principles of the socio-ecological systems framework, this study aims to formulate a sustainable management strategy for Telaga Cebong by integrating community perspective, ecological data, and institutional frameworks. We hypothesize that the successful formulation of a sustainable management strategy for Telaga Cebong requires prioritizing formal institutional and policy interventions (AHP weight >50%) which are supported by strong community engagement. Methods: Using a mixed-methods case study approach, the research combines qualitative Strengths, Weaknessess, Opportunities, and Threaths (SWOT) analysis with the Analytical Hierarchy Process (AHP) to prioritize strategic interventions. Data were collected through field observation, in-depth interview, structured questionnaires, and secondary data. Findings: The Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices revealed that strengths and opportunities dominated the strategic landscape. AHP result showed that the Policy and Institutional Strategy received the highest priority weight (53,3%), followed by Human Resource Capacity, Cultural Values, and Government-Community Partnership. Conclusion: These findings confirm that formal governance mechanisms, supported by community engagement, are essential for long-term sustainability. Novelty/Originality of this article: This study contributes a novel SWOT-based framework that integrates participatory insights with multi-criteria decision-making to guide ecosystem management in rural freshwater context.